Non-contrast enhanced visualization of the equine foot vasculature in a cadaver model using time-of-flight sequence - Underberg, Bianca A.; Kaessmeyer, Sabine; Schweizer, Daniela; Drews, Barbara; Van der Vekens, Elke (Frontiers in Veterinary Science, 2025)
ObjectiveThe objective of this study was to establish a non-contrast enhanced MR angiography (NC-MRA) sequence for the equine foot (EF) using a post-mortem angiography model.Materials and methodsTime-of-flight (TOF) sequences were tested using variable parameter settings and 3 slice orientations during vascular perfusion of frozen–thawed cadaver EF with paraffine oil. Transverse and dorsal orientations were planned perpendicular or parallel to the sublamellar vascular plexus at the dorsal aspect of P3, or approximately perpendicular to the coronary plexus. Visibility of the coronary plexus, sublamellar plexus, palmar plexus, terminal arch and its respective branches, solar plexus, and the marginal circumflex vessels was evaluated in a total of 74 sequences.ResultsTwelve EF of 10 horses were scanned. Visibility of vessels as small as the sublamellar plexus was best achieved by 3D-TOF sequences in transverse and dorsal orientations with the following parameters: pixel size 0.34 × 0.48 mm, slice thickness 0.2 mm, interslice gap 0.2 mm, TR/TE 21.2/4.7 ms, flip angle 16°, TONE ramp 70%, acquisition time 22.05 min. Only for the sublamellar plexus, the transverse acquisition showed a slightly better visualization than the dorsal acquisition, however the latter could include nearly the entire EF in the field of view with the same acquisition time.Conclusion and discussion3D-TOF allowed visualization down to at least the sublamellar venous plexus which is reported to have diameters of approximately 0.45 mm. The post-mortem model facilitated establishment of a TOF sequence without the need for experimental animals.